Pre-admission antiplatelet therapy and treatment effect of ticagrelor vs. prasugrel in patients with acute coronary syndromes: a subgroup analysis of the ISAR-REACT 5 trial : original article : acute coronary syndromes - Lahu, Shqipdona; Ndrepepa, Gjin; Neumann, Franz-Josef; Menichelli, Maurizio; Bernlochner, Isabell; Richardt, Gert; Wöhrle, Jochen; Witzenbichler, Bernhard; Hemetsberger, Rayyan; Mayer, Katharina; Akın, Ibrahim; Cassese, Salvatore; et al. (European heart journal - cardiovascular pharmacotherapy, 2022)
To assess whether the efficacy and safety of ticagrelor vs. prasugrel in patients with acute coronary syndromes (ACSs) are influenced by pre-admission treatment with aspirin and/or clopidogrel.Patients (n = 4018) were categorized into two groups: pre-admission aspirin and/or clopidogrel group (n = 1455) and no pre-admission aspirin or clopidogrel group (n = 2563). The primary endpoint was the composite of all-cause death, myocardial infarction, or stroke; the secondary safety endpoint was Bleeding Academic Research Consortium (BARC) type 3-5 bleeding, both at 1 year. Patients in the pre-admission aspirin and/or clopidogrel group had a higher risk of ischaemic events, but a similar risk of bleeding to patients in the no pre-admission aspirin or clopidogrel group (cumulative incidences 10.5% vs. 6.7%, and 5.7% vs. 5.7%, respectively). The primary endpoint occurred in 81/717 patients assigned to ticagrelor and 69/738 patients assigned to prasugrel in the pre-admission aspirin and/or clopidogrel group [11.5% vs. 9.5%; hazard ratio (HR) = 1.23; 95% confidence interval (CI) 0.89-1.69], and in 103/1295 patients assigned to ticagrelor and 68/1268 patients assigned to prasugrel in the no pre-admission aspirin or clopidogrel group [8.0% vs. 5.4%; HR = 1.50 (1.10-2.03); Pint = 0.38]. BARC type 3-5 bleeding events did not differ between ticagrelor and prasugrel in patients in the pre-admission aspirin and/or clopidogrel (6.2% vs. 4.5%) or no pre-admission aspirin or clopidogrel (5.3% vs. 5.1%) group (Pint = 0.54).In patients with ACS, pre-admission therapy with aspirin and/or clopidogrel has no influence on the relative efficacy and safety of ticagrelor and prasugrel.
Gesehen am 26.09.2023